An analysis of common Guillemot Uria aalge chick diet, Atlantic Puffin Fratercula arctica productivity, and Great Skua Stercorarius skua diet on Mingulay, Outer Hebrides - Lawrence, Sarah Elizabeth, 1989- (2015)
Mingulay hosts nationally important congregations of several seabird species. Regular seabird monitoring has recently been established, and this study aimed to improve the current state of knowledge for three species. The study investigated common guillemot Uria aalge chick diet, great skua Stercorarius skua diet, and conducted an Atlantic puffin Fratercula arctica productivity study and census count. Sandeel stocks around the UK are changing, due to both fisheries and climate change. As a keystone species, the impacts of these changes are complex, and common guillemot chick diet acts as an indicator of sandeel availability. This study found that chick diet on Mingulay consists mainly of sandeels and gadoids. Later in the season, the proportion of sandeels in chick diet decreased, while gadoids increased significantly. Gadoids are the predominant alternative prey type, and if sandeel availability declines as a result of climate change then common guillemot chick survival could suffer, as gadoids are of lower nutritional value. Great skua diet was analysed to collect baseline data that can allow the impacts of increasing population and a reduction in fisheries discards to be understood. This study found seabird remains in 88% of pellets analysed, suggesting that great skuas on Mingulay predate heavily on other seabirds. The impact on black-legged kittiwakes is particularly concerning, as this species is suffering long-term decline on Mingulay, as well as nationally. The census and productivity study of Atlantic puffins at Mingulay Bay identified 893 Apparently Occupied Burrows in early June. This figure is consistent with recent census counts, and suggests that the population is stable. Puffin productivity was calculated as 0.594 ± 0.153. This figure suggests that 2014 was a successful season for puffins on Mingulay, compared to 2013 when productivity was 0.158 ± 0.164. These studies can contribute to management decisions on Mingulay; as part of a long-term dataset, the studies can reveal trends in dietary ...